Perancangan Sistem Photovoltaic untuk Mesin Pembuat Es di Pelabuhan Perikanan Sadeng - Arif Rahman Hakim; Widiarto Sarwono; Luthfi Assadad (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2018)
Currently, requirement of ice as medium fish cooling in PP Sadeng has not been fulfilled. This causes deterioration of fish quality when received by the consumers. The self production of ice blocks using ice maker machine has not solved this problem due to the highly operating costs, especially fuel. Photovoltaic (PV) systems are expected to overcome this problem. PV systems have high potential, since it is clean, environment-friendly, secure, and renewable. This paper explains the stages of PV system design, including PV module size, battery, solar charge controller, inverter, and also economic feasibility analysis. The results show that energy requirement of ice maker machines is 19,383.60 watts. The PV system consists of 40 units of 260 wp PV module, 82 units of battery 12V 100AH, 11 units of solar charge controller 40 A type MPPT, and 20 units of inverter DC-AC pure sine wave 1,200 W. Economic analysis shows that the life cycle cost (LCC) PV system designed is Rp513,704,165 for 25 years and levelized cost of energy (LCOE) of PV system is Rp1,401 per kWh.